Unimodular gravity theory with external sources in a Lorentz-symmetry breaking scenario - Borges, L. H.C. [UNESP]; Dalmazi, D. [UNESP] (American Physical Society (APS), 2019)
This paper is dedicated to the study of interactions between stationary field sources for the linearized unimodular gravity or the Weyl plus transverse diffeomorphism (WTDIFF) theory in a model that exhibits Lorentz-symmetry breaking due to the presence of the linearized topological Chern-Simons term in 3+1 dimensions, where the Lorentz symmetry breaking is caused by a single background vector vμ. Since the background vector is very tiny, we treat it perturbatively up to second order and we focus on physical phenomena which have no counterpart in standard WTDIFF theory. We consider effects related to field sources describing pointlike particles and cosmic strings. We show that in a Lorentz-violating scenario the interaction between external sources lead to numerically different results for the linerarized Eintein-Hilbert and WTDIFF theories; however, both results are qualitatively similar and can be equalized after a rescaling of the Lorentz-breaking source term which makes an experimental distinction impossible at leading order in pertubation theory as far as point particles and cosmic strings are concerned.